Fiscal Decentralization, Financial Performance, and Human Development: Evidence from Central Kalimantan - Trisna, Maria (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Fiscal decentralization is increasingly recognized as a strategic instrument for strengthening local financial capacity and improving the quality of public service delivery, which ultimately plays a decisive role in enhancing human development index outcomes in regions such as Central Kalimantan. This study investigated the causal relationship between fiscal decentralization, financial performance, public service efficiency, and the human development index in Central Kalimantan. This study used a quantitative approach and Smart-PLS as analysis tools. Utilizing panel data from 14 districts/cities over the 2020–2024 period, the research reveals that both fiscal decentralization and financial performance significantly and positively influence public service efficiency and the human development index. Public service efficiency itself exerts a substantial direct impact on the human development index and serves as a significant mediating variable, amplifying the indirect effects of fiscal and financial governance. Model fit indices confirm the robustness of the structural model. The findings underscore that efficient public service delivery is a critical pathway through which fiscal capacity and financial management translate into human development outcomes. These insights provide a strategic foundation for enhancing fiscal autonomy, improving service delivery, and accelerating human development in decentralized regions.